Analysis on losses and boiler efficiency to find optimum cooling water flowrate - Mohd Shahrulnizam, Abu Seman (2007)
Steam power plant is using fuel to generate electrical power. The used of the fuel must be efficient so the boiler can generate for the maximum electrical power. By the time the steam cycle in the boiler, it also had heat losses through some parts and it effect on the efficiency of the boiler. This project will analyze about the parts losses and boiler efficiency to find the optimum cooling water flowrate. By using the CUSSONS P7690/SP steam power plant in mechanical laboratory in UMP the data is collect by using 4 types of cooling water flowrate that is 30001/h, 40001/h, 50001/h and 60001/h. Result of the analysis show that the optimum cooling water flowrate for superheated steam is 60001/h that give lowest losses, 6.1 kW and maximum efficiency that is 78.99%. This study is fulfilling the objective of analysis to find the optimum cooling water flowrate for steam power plant in liMP.